STUDIES ON HOST PREFERENCE OF PARASA LEPIDA ON SOME CULTIVARS OF HYBRID COCONUT IN SWAMPY AREA - Wily A. Baringbing; Bariyah Baringbing (CORD, 1994)
A two‑month f ield experiment to study host preference of the leaf‑eating caterpillar, Parasa lepida cramer, on 5 cultivars of hybrid coconut: Green Khina‑1, Brown Khina‑1, Nias Yellow Dwarf (NYD) x West African Tall (WAT),. Malayan Red Dwarf (MRD) x WAT, and Camerun Red Dwarf (CRD x Rennel Tall (RLT), aged 2.5 years, was carried out in swampy area of South Sumatra province, in 1991.